Transformation Of Generation Z Tourism Management In Visiting Halal Tourism In Banda Aceh City - Ismail, Ismail; Lisnawati, Lisnawati (Jurnal Ekonomi, 2024)
Halal tourism is considered a subcategory of religious tourism that was born from the concept of religious tourism which covers all aspects of a Muslim's life. Generation Z is identified as a generation that is very instrumental in growth, especially in the growth of halal tourism. The purpose of the study was to analyze the factors that influence Generation Z in doing halal tourism to Banda Aceh. This research uses quantitative methods with SEM (Structural Equation Modeling) approach. Development strategy through SWOT analysis. Based on the results of the study that the location variable on the decision of generation Z tourists has a significant effect. Based on the results of the calculation, the coordinate points are in quadrant I. The strategy to be used if it is in quadrant I is an aggressive strategy. This aggressive strategy (S-O) is carried out by utilizing existing opportunities with its strengths such as the atmosphere of tourist attractions providing comfort, friendly service, tourist attractions suitable for all groups, and the facilities provided at Halal Tourism Objects in the city of Banda Aceh are quite good. From the results of the calculation of IFAS and EFAS factors, several alternative strategies can be generated in marketing and managing Halal Tourism Objects in the city of Banda Aceh in supporting more effective marketing and management.